Interactive Learning for Teaching Physics Subjects at MA Nurul Huda Talang, Saronggi, Sumenep, Madura - Yuniar Mughayyirah; Nadziratul Ulya; Imam Anas Mubarok (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Physics is a subject that students are less interested in because it has a high level of difficulty in understanding, so to increase students interest and sympathy for physics, learning media that is interesting and not monotonous is needed. However, the reality in the field is that there are still very few teachers who have the skills and abilities to develop interesting learning media such as interactive learning media such as